The postoperative management of percutaneous aortic valve implantation with the use of anticoagulants and platelet antiaggregants: A review of the literature (Research, Society and Development, 2021)
Introduction: One of the main treatments of aortic stenosis can be done through a surgical procedure, "open chest", the aortic valve replacement surgery (SAVR). However, patients classified as high risk and/or with severe symptoms are unable to undergo it, decreasing their survival. Because of this, minimally invasive alternatives have emerged, such as transcatheter aortic valve implantation (TAVI). One of the postoperative management of this patient is with oral anticoagulant therapy. Objective: To know the main anticoagulants used in TAVR postoperative period. Methodology: This is a descriptive study, of the literature review type, through the following databases: Scielo, Pubmed and Science Direct. Results: The articles sought to clarify the pathophysiology of aortic stenosis, as well as its diagnosis and treatment. These articles allowed us to identify the mechanism of action of anticoagulants used in the postoperative period of TAVR. Conclusion: The synthesis of knowledge about the management of anticoagulant therapy after TAVR may support actions of medical professionals in order to avoid non-physiological events.